Comparison of different drug regimens for the treatment of loiasis—A TropNet retrospective study - Gobbi, Federico; Bottieau, Emmanuel; Bouchaud, Olivier; Buonfrate, Dora; Salvador, Fernando; Rojo-Marcos, Gerardo; Rodari, Paola; Clerinx, Jan; Treviño, Begoña; Herrera-Ávila, Juan Paulo; Neumayr, Andreas; Calleri, Guido; et al. (PLOS Neglected Tropical Diseases, 2018)
Background Loa loa infection is endemic in limited areas of West-Central Africa. Loiasis has been associated with excess mortality, but clinical studies on its treatment are scant, particularly outside endemic areas, due to the rarity of cases diagnosed. Methodology/Principal findings With this retrospective TropNet (European Network for Tropical Medicine and Travel Health) study, we aimed at outlining the treatment schedules followed by different reference centers for tropical medicine across Europe. We gathered information about 238 cases of loiasis, 165 of which had follow up data. The regimens followed by the different centers were heterogeneous. The drugs most frequently administered were: diethylcarbamazine alone (74/165, 45.1%), ivermectin alone (41/165, 25%), albendazole + ivermectin (21/164, 11.6%), ivermectin + diethylcarbamazine (16/165, 9.7%). Conclusions/Significance The management of loiasis substantially differs across specialized travel clinics in Europe. These discrepancies could be due to different local protocols as well as to (un)availability of the drugs. An harmonization of clinical protocols for the treatment of loiasis would be suggested across reference centers for tropical medicine in Europe.